A Metacognitive Framework for NCLEX and Nursing Exam Remediation: From Cognitive Traps to Reasoning Repair - Angela K. Capello (Nurse Educator, 2026)
Background: Nursing students may complete extensive National Council Licensure Examination practice yet continue to repeat similar errors, suggesting that missed questions may reflect breakdowns in cue recognition, prioritization, distractor evaluation, or uncertainty management rather than content gaps alone. Problem: Traditional National Council Licensure Examination preparation often emphasizes content review, rationales, and repeated exposure to questions. While valuable, these strategies may not help students identify how their thinking was pulled off track, leading remediation to become answer review rather than pattern correction. Approach: This article introduces the Reasoning Repair Framework , a student-facing metacognitive remediation model that helps students identify cognitive traps, reconstruct reasoning, and transfer stronger thinking patterns. The framework addresses 8 traps and uses a 6-step process: reconstruct the task, identify cues, analyze distractors, recognize the trap, rebuild reasoning, and transfer the corrected pattern. Conclusions: The framework reframes missed questions as cognitive data, shifting remediation from content repetition to cognitive reconstruction, metacognitive awareness, and clinical judgment development.